Baggage Claim in Airports using Near Field Communication - Mikhael Bagus Renardi; Kuspriyanto Kuspriyanto; Noor Cholis Basjaruddin; Anton Prafanto (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The popularity of public transportation has increased as infrastructures have been repaired and other supporting facilities have been added. One of the facilities which can be added in the transportation system is the implementation of Near Field Communication in order to accelerate each transaction in the transportation system. In airports, transaction activities need to be done efficiently, like claiming baggage at the baggage carousel. The speed of transaction to claim the baggage depends on the number of officers, passengers, and the amount of baggage brought by the passengers. In the conventional system, the most effective way of getting the maximum speed of transaction is to have officers as many as the number of passengers, but this is not efficient regarding the use of human resources. The use of Near Field Communication can solve the problem related to the efficiency of resources, safety, and the increasing speed of transaction.